Relationship Between Dermatoglyphic Patterns and ?-Thalassemia Major Disease - Nisa'u Luthfi Nur Azizah; Selfi Handayani; Nanang Wiyono (Nexus Kedokteran Translasional, 2015)
Background: ?-Thalassemia major is the most common severe thalassemic disease in the world. Children with ?-Thalassemia major have to be identified and treated soon to prevent the worse prognosis of the disease. One of the screening methods to establish thalassemic diagnosis is by observing dermatoglyphic patterns. The aim of this study was to determine the relationship between dermatoglyphic patterns and ?-Thalassemia major disease. Methods: This study was an observational analytic study with cross sectional design. This study located in Poliklinik Anak and SMF Anak RSUD Dr. Moewardi Surakarta. The sampling technique used purposive sampling based on the characteristics of population that have been known previously. The subjects were 20 patients of ?-Thalassemia major and 20 non- ?-Thalassemia major. Data were obtained through direct scanning the subjects fingerprints using scanner. Statistical analysis used independent-sample t test, Mann-Whitney test and chi square test. Results: From the analysis, this study found there was no significant difference of the ridge count between patients and control group (p > 0.05). However, there was significant difference of the patterns between patients and control group (p < 0.05). The number of whorl patterns in ?-Thalassemia major patients was 53,5%, it greater than that in normal individuals (20,5%). Loop patterns were less frequent in ?-Thalassemia major patients (34%) compared to normal individuals (75,5%). Arch patterns had no significant difference between patients and control group (p > 0.05). Conclusions: There was a significant relationship between dermatoglyphic patterns and ?-Thalassemia major disease. Keywords: ?-thalassemia major, dermatoglyphic, fingerprint